Análise térmica computacional do Transponder 40Gbps PADTEC - Paschoalini, Amarildo Tabone [UNESP]; Bazani, Márcio Antonio [UNESP]; Shinoda, Ailton Akira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents the computational thermal analysis of 40Gbps Transponder equipment in subrack 9U and 4U high. The specific objectives were to detect critical operating temperatures, optimizing the positioning of electronic components on printed circuit boards and optimizing the model, quantity and the positioning fans in the system.

Este trabalho apresenta a análise térmica computacional do equipamento Transponder 40Gbps em sub-bastidor de 9U e 4U de altura. Os objetivos específicos foram a detecção de temperaturas máximas de operação, otimização do posicionamento de componentes eletrônicos nas placas de circuito impresso e otimização do modelo, da quantidade e do posicionamento de ventiladores no sistema.
Keywords: Thermal analysis; Computational modeling; Optical communications; Análise térmica; Modelagem computacional; Comunicações ópticas